(untitled) (Altre Modernità, 2022)
Toys with non-anthropomorphized features in literature, especially when addressed to a children’s readership, prove to be a useful tool in reflecting on the distinction between the ‘human’ and the ‘non-human’. Indeed, the artificial body of the toy and its animal characterization embody in a clear fashion the concept of otherness compared to the stereotypical idea of humanity. Inspired by these stories, children might learn essential lessons, such as the capacity for empathy and resilience to those small or big traumas that anyone is called to meet during his/her lifetime. The critical introduction to these reflections is completed by the literary analysis about the characterization of toys in some children’s books: the rabbit-toy in The Velveteen Rabbit (1922) di Margery Williams, the mice-toys in The Mouse and His Child (1967) di Russell Hoban, and the bear-toy in Winnie-the-Pooh (1926) di A. A. Milne.